Patterns and motivations for method choices in suicidal thoughts and behaviour: qualitative content analysis of a large online survey. Issue 2 (24th February 2021) - Marzano, Lisa; Katsampa, Dafni; Mackenzie, Jay-Marie; Kruger, Ian; El-Gharbawi, Nazli; Ffolkes-St-Helene, Denika; Mohiddin, Hafswa; Fields, Bob
Abstract : Background: Choice of suicide method can strongly influence the outcome of suicidal behaviour, and is an important aspect of the process and planning involved in a suicide attempt. Yet, the reasons why individuals consider, choose or discard particular methods are not well understood. Aims: This is the first study to explore method choices among people with a history of suicidal behaviour and individuals who have experienced, but not enacted, suicidal thoughts. Method: Via an online survey, we gathered open-ended data about choice of methods in relation to suicidal thoughts and behaviours, including reasons for and against specific means of harm. Results: A total of 712 respondents had attempted suicide, and a further 686 experienced suicidal thoughts (but not acted on them). Self-poisoning was the most commonly contemplated and used method of suicide, but most respondents had considered multiple methods. Method choices when contemplating suicide included a broader range of means than those used in actual attempts, and more unusual methods, particularly if perceived to be lethal, 'easy', quick, accessible and/or painless. Methods used in suicide attempts were, above all, described as having been accessible at the time, and were more commonly said to have been chosen impulsively. Key deterrents against the use of specific methods were the presence of and impact on other people, especially loved ones, and fears of injury and survival. Conclusions: Exploration of method choices can offer novel insights into the transition from suicidal ideation to behaviour. Results underscore the need for preventative measures to restrict access to means and delay impulsive behaviour.